Hepatitis B virus: A new platform for in vitro studies of infection, replication cycle and pathogenesis - da Cruz, Carla Rios [UNESP]; Lopes, Rute [UNESP]; Santana, Moema de Souza [UNESP]; da Costa, Paulo Inácio [UNESP] (Editora Cubo, 2020)
Hepatitis B virus (HBV) research has been hampered by the lack of suitable and reproducible cell culture systems that reliably mimic the viral life cycle. Several infection stages and metabolic aspects related to HBV cycle still need to be elucidated. The aim of this research was the study of techniques aiming at developing a sustainable in vitro platform of hepatitis B virus infection, in a simplified and low maintenance approach, evaluating the continuity of infection in cell culture throughout many passages, using a positive serum pool to the virus in human hepatocellular carcinoma. The viral load was quantified by real-time polymerase chain reaction. The cells underwent a freeze and thaw cycle, followed by seeding, and the new culture was analyzed to quantify the viral load. An aliquot was used to detect the surface antigen (HBsAg), by chemiluminescence. The detection of the core antigen (HBcAg) was performed by flow cytometry and by immunofluorescence microscopy. Viral load remained detectable throughout the studied period, 50 days after initial infection. The process of freezing and seeding produced detectable viral load for a 7-day period. HBsAg was reagent in the infected cells, confirming the maintenance of infection. The flow cytometry result indicated 11.85% of HBcAg positive cells, which demonstrates that new viral particles were at the assembly stage. Indirect immunofluorescence using epiluminescence microscopy allowed the detection of viral HBcAg in the interior of infected cells, confirming the results obtained by flow cytometry. The platform for infection in cell culture was successfully obtained during the studied period, which represents the possibility to apply this model in a continuous practice, to support several biotechnological purposes.
Keywords: Cell Culture; Hepatitis B; Hepatocellular Carcinoma Cells; In vitro Infection